Technical Debt of Usability in Software Projects: A Multi-Case Study - Lage, Luiz Carlos da Fonseca; Trevisan, Daniela G.; Kalinowski, Marcos (iSys - Journal of Information Systems, 2020)
Background: Over the years, several studies were conducted aiming at understanding the Technical Debt (TD) phenomenon and its implications on software development. Most of these studies focus on source code related TD types. The absence of empirical studies on usability debt motivated our research. Aims: The goal of this paper is to provide an initial usability debt characterization in software projects regarding its occurrence, type, and resolution effort. Method: We conducted a multi-case study, analyzing TD items of five software projects from four Brazilian public companies. Results: After several steps of selection, classification, and validation, we identified 145 TD items in the change management systems used in the projects. The analysis of these items allowed us to observe that 13.8% of the TD items concerned usability debt (ranging from 10.4% to 20.8% in the five projects). The identified usability debt items cover a range of relevant usability issues, violating eight out of the ten Nielsen usability heuristics. Regarding effort for paying the TD, measured in man hours estimated by the project managers for resolving the TD items, usability debt items require a relatively low effort, ranging from 5.1% to 6.7% of the total TD resolution effort in the analyzed projects. Conclusions: Considering that usability TD items are frequent, concern relevant usability issues and require low effort for their payment, we put forward that actions for identifying and paying this type of TD should receive high priority in TD management strategies.